IMPLEMENTATION OF ANDROID FREE EDUCATIONAL GAMES AS A LEARNING MEDIUM FOR THE INTRODUCTION OF HIJAIYAH LETTERS AT THE ELEMENTARY SCHOOL LEVEL - Tri Susanti (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
The purpose of this research is to develop an Android-based educational game to introduce elementary school students to the nature of hijaiyah letters in an interactive and fun way. The development method uses the Game Development Life Cycle (GDLC) through six stages: initialization, pre-production, production, testing, beta release, and final release. Testing was carried out using alpha testing by experts and beta testing by students, using the Likert scale and N-Gain calculations. The results of alpha testing showed that the application's feasibility was 88.4% for materials and 86.6% for media. Meanwhile, the N-Gain results showed an increase in student understanding from a pretest score of 58.2 to a posttest score of 85.4, placing it in the high effectiveness category. Thus, this application is considered feasible and effective as an interactive learning medium for recognizing the nature of hijaiyah letters.